PENGARUH INSENTIF TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL MODERASI (Studi pada Agen PT. Jiwasraya Kantor Cabang Malang Kota) - Galaxy Mustofa (Universitas muhammadiyah malang, 2017)
The purpose of the study describes the incentive, motivation and performance of employees at PT. Jiwasraya Malang Branch Office City, analyzed the effect of incentives on employee performance with motivation as a moderating variable. Sample research is a marketing agent assosiate amounting. Sampling using Total Sampling technique.. Simple linear regression analysis to determine the effect between incentive variable and employee performance. Moderate analysis to find out the moderation relationship between the influence of incentives on employee performance. The results showed that employee performance in very low category, incentives enter in good category and motivation included in low category. Incentives affect employee performance. Motivation variable moderate the influence of incentive to employee performance. Moderate variables increase the percentage of influence of employee incentives and performance which means motivation strengthen the influence of incentives on employee performance.